Scattered Finds Archaeology, Egyptology and Museums - Stevenson, Alice (UCL Press, 2019)
Scattered Finds explores the politics, personalities and social histories that linked fieldwork in Egypt with the varied organizations around the world that received finds. Case studies range from Victorian municipal museums and women's suffrage campaigns in the UK, to the development of some of the USA's largest institutions, and from university museums in Japan to new institutions in post-independence Ghana. By juxtaposing a diversity of sites for the reception of Egyptian cultural heritage over the period of a century, Alice Stevenson presents new ideas about the development of archaeology, museums and the construction of Egyptian heritage. She also addresses the legacy of these practices, raises questions about the nature of the authority over such heritage today, and argues for a stronger ethical commitment to its stewardship.